SURVEY ON HEART DISEASE PREDICTION SYSTEM USING DATA MINING TECHNIQUE - AMRUTA POWAR; PROF. DR. VIJAY GHORPADE (International Journal of Innovations in Engineering Research and Technology, 2021)
According to WHO maximum death in worldwide are happened due to heart disease. So, advanced data mining techniques can be used to take out hidden patterns from healthcare industry, so that it becomes easy to predict heart disease. In this paper we considerthe concepts used for prediction of heart disease using data mining techniques. Human heart disease Prediction using variousdata mining techniques, their comparative result and their limitations are discussed here. This paper gives an idea about the key topics for heart disease prediction system which will help in predicting heart disease so that diagnosing it can take less medical tests and provide effective treatments.